1999
DOI: 10.1103/physrevstab.2.054201
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb scattering within a spherical beam bunch in a high current linear accelerator

Abstract: Beam halo formation issues are important for the design of high current linear ion accelerators. Various mechanisms can potentially cause beam halo. Some recent studies suggested that Coulomb collisions in the beam bunch can contribute significantly to beam bunch growth and halo development in linear accelerators. Despite the general belief that collisions are not important, it is clear that a rigorous treatment of this question is needed. In an effort to explore this issue in detail we have undertaken an anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…While analytical theory [3,4] indicated that space-charge-dominated beams were unstable to collective modes, particle-in-cell computer simulations showed all but one of these modes stabilizing nonlinearly and quickly, with negligible heating of the beam. The Single Beam Transport experiment [5] showed that the simulations were correct, and delineated the stable regime for propagation.…”
Section: Status Of Heavy-ion Fusion Physicsmentioning
confidence: 99%
“…While analytical theory [3,4] indicated that space-charge-dominated beams were unstable to collective modes, particle-in-cell computer simulations showed all but one of these modes stabilizing nonlinearly and quickly, with negligible heating of the beam. The Single Beam Transport experiment [5] showed that the simulations were correct, and delineated the stable regime for propagation.…”
Section: Status Of Heavy-ion Fusion Physicsmentioning
confidence: 99%
“…E-mail: fjq96@iris.ciae.ac.cn beam spill below parts in 10-5-10-8/m, have to be satisfied in the applications. Therefore, the study of halochaos has become one of the key issues which a focusing research subject has been formulated on developing new high-power accelerators (Gluckstern, 1994;Chen and Davidson, 1994;Lagniel, 1994;Fink and Chen, 1997;Gluckstern et al, 1998;Gluckstern and Fedotov, 1999;Fedotov and Gluckstern, 1999; Wang, 1999;Fang, 2000). In this area, what needs to be resolved includes not only a better understanding mechanisms of beam halo-chaos formation but also its suppression and control.…”
Section: Introductionmentioning
confidence: 99%
“…We then related our analysis to diffusion caused by many small angle Coulomb collisions, with the conclusion that the effect of multiple Coulomb collisions in halo development in high current ion accelerators is also expected not to be important [28].…”
Section: Coulomb Scatteringmentioning
confidence: 99%
“…Despite the general belief that collisions are not important it is clear that a rigorous treatment of this question is needed. In an effort to explore this issue in detail we have undertaken an analysis of the effects of Coulomb scattering between ions in a self-consistent spherical bunch [28]. We have calculated the effect of single Coulomb scattering of a self-consistent 6-D distribution for a spherical beam bunch.…”
Section: Coulomb Scatteringmentioning
confidence: 99%